Seputar Antropologi Agama; Pandangan Tentang Islamologi Aplikatif Muhammad Arkoun - Prakoso, Tjahyo Adji (Universitas Islam Negeri Raden Intan Lampung, 2023)
Abstract;Islam has various dimensions, one of the dimensions in the Islamic religion is the anthropological dimension. This dimension is the main point of development of Islam in society and is carried out through patterns that are interrelated and cause and effect, namely doctrinal patterns and discursive patterns. In an applied context, the study of Islamic Anthropology forms a religious identity that guarantees the continued function and role of religion for its adherents. On the other hand, in a discursive context, Islamic studies form a religious rationality that guarantees the construction of arguments on the substance, function and role of religion for society. For Arkoun, the problem of West and East is a problem of methodology and epistemology. Therefore, to build contemporary Islamic reasoning, Arkoun invites cooperation between West and East, in an applied form. This research also uses a conceptual approach that includes: Anthropology and Applicative Islamology. The conclusion is that applicable Islamology is the result of Arkoun's thinking about the shortcomings in classical Islamic scholarship contained in the occasional discourse (discourse or way of Western Islamology towards Islam), a discourse that tries to understand Islam rationally, but is less critical. Or another term that is more general but less liked by Arkoun is orientalism.Keywords:Abdul Qadir al-Jailani; Modernity; Moral Interpretation. Abstrak;Islam memiliki ragam dimensi, salah satu dimensi yang ada di dalam agama Islam adalah dimensi antropologi. Dimensi ini menjadi titik utama pengembangan Islam di masyarakat dan dilakukan melalui pola yang saling terkait dan menimbulkan sebab-akibat, yaitu pola doktrinasi dan pola diskursif. Dalam konteks aplikatif, studi Antoropologi Islam membentuk identitas keagamaan yang menjamin keberlangsungan fungsi, dan peran agama bagi penganutnya. Sebaliknya dalam konteks diskursif, studi Islam membentuk rasionalitas keagamaan yang menjamin tegaknya konstruksi argumentasi subtansi, fungsi dan peran agama bagi masyarakat. Permasalahan Barat dan Timur ini bagi Arkoun adalah permasalahan metodologi dan epistemologi. Oleh karena itu, untuk membangun nalar Islam kontemporer Arkoun mengajak kerjasama antara Barat dan Timur, dalam bentuk aplikatif. Penelitian ini juga menggunakan pendekatan konsep yang mencakup: Antropologi dan Islamologi Aplikatif. Kesimpulannya adalah Islamologi aplikatif adalah hasil pemikiran Arkoun atas kekurangan-kekurangan di dalam keilmuan-keilmuan Islam klasik yang termuat dalam discours occidental (wacana atau cara Islamologi Barat terhadap Islam), sebuah wacana yang mencoba memahami Islam secara rasional, namun kurang kritis. Atau istilah lain yang lebih umum namun kurang disukai oleh Arkoun adalah orientalisme.Kata Kunci: Abdul Qadir al-Jailani; Modernitas; Tasawuf Akhlaqi.